An Anti-Prophet among the Prophets?: On the Relationship of Jonah to Prophecy - Schellenberg-Lagler, Annette (Journal for the study of the Old Testament, 2015)
Despite the fact that the book of Jonah and its main character are atypical compared to other prophetic books and prophets, the book became one of the Twelve. Taking up insights from Ehud Ben Zvi and others, this article argues that these idiosyncrasies have to do with the self-understanding of the authors/tradents of the book and their ambivalent relationship to the classical prophetic past of ancient Israel. Identifying them as ‘literary prophets’, indebted to the prophetic tradition but at the same time aware of the differences from their classical predecessors, helps explain the ambivalences in the portrayal of Jonah, the interest in meta-prophetic questions, and peculiarities like the literary form of the book and the choice of Nineveh as the city that escaped destruction.